2020
DOI: 10.21037/tro-20-22
|View full text |Cite
|
Sign up to set email alerts
|

Patients with cervical cancer without visceral obesity had better treatment outcomes

Abstract: Background: Obesity is associated with malignant tumor development and may affect cancer outcomes.This study is to assess the relationship between the visceral fat-subcutaneous fat ratio (V/S ratio) and overall survival (OS) in cervical cancer patients.Methods: We studied the data of patients with stage I-III cervical cancer who received definitive concurrent chemoradiotherapy (CCRT) from 2010 to 2013 at a single institution. Their visceral and subcutaneous fat areas were delineated from simulated CT images ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Instead, we demonstrated that the The clinical significance of visceral fat area depends on the type of malignancy. While higher visceral fat was significantly associated with better OS in gastric cancer [14], a higher visceral to subcutaneous fat ratio was significantly associated with worse OS in uterine cervical, pancreatic, and metastatic colorectal cancer [15][16][17].…”
Section: Discussionmentioning
confidence: 94%
“…Instead, we demonstrated that the The clinical significance of visceral fat area depends on the type of malignancy. While higher visceral fat was significantly associated with better OS in gastric cancer [14], a higher visceral to subcutaneous fat ratio was significantly associated with worse OS in uterine cervical, pancreatic, and metastatic colorectal cancer [15][16][17].…”
Section: Discussionmentioning
confidence: 94%